Risk of bowel ischemia in patients with mesenteric neuroendocrine tumors after treatment with 177Lu-DOTATATE - Eleonora Pelle; Taymeyah Al-Toubah; Ghassan El-Haddad; Brian Morse; Bhavana Konda; Vineeth Sukrithan; Jonathan Strosberg (Endocrine Oncology)
Background: Lutetium-177 (177Lu)-DOTATATE is an effective treatment for metastatic gastroenteropancreatic (GEP) NETs. However, radiation can cause transient inflammation/swelling of tumors, which can result in toxicity. Treatment-related small bowel obstruction associated with mesenteric or peritoneal disease has been described. We investigated the potential for intestinal ischemia in 177Lu-DOTATATE-treated patients. Methods: Clinical records were reviewed of patients with midgut NETs treated with 177Lu-DOTATATE at the Moffitt Cancer Center between April 2018 and December 2022 and at The Ohio State University between December 2017 and October 2020. Results: Among the cases reviewed, we identified three patients who developed bowel ischemia/perforation shortly after their initial treatment with 177Lu-DOTATATE. All patients had metastatic small bowel NET with prominent mesenteric mass encasing/obstructing the mesenteric vessels and preexisting symptoms of postprandial abdominal pain. Conclusion: Acute bowel ischemia may be a rare complication of PRRT in patients with mesenteric arterial or venous obstruction from mesenteric metastasis.